European Local Pig Breeds - Diversity and Performance (IntechOpen, 2023)
Local or autochthonous pig breeds represent a pool of genetic diversity of porcine species and a link with old-style traditional production systems and traditional pork products. These breeds were largely abandoned because they were not competitive in the concept of modern, industrial type of pig production. Despite an increased interest for local pig breeds in the past years, they remain largely untapped and the knowledge about their characteristics is limited, which was a challenge undertook in the project TREASURE in the frame of multicriteria evaluation of local pig breeds. The book represents a valuable compendium of data on census, breeding organisations, production systems, and performances with ambition to present their contemporary (preserved) phenotype. This work has received funding from the European Union’s Horizon 2020 research and innovation programme under grant agreement No 634476 for project with acronym TREASURE. The content of this book reflects only the authors' view and the European Union Agency is not responsible for any use that may be made of the information it contains.